The Swahili Coast and the Indian Ocean Trade Patterns in the 7th–10th Centuries CE. Issue 5 (3rd September 2017) - Pollard, Edward; Kinyera, Okeny Charles
Abstract : This article investigates foreign trading patterns along the east African or Swahili coast in the late 1st millennium CE. It is based on recent archaeological investigations around Bagamoyo and Kilwa in Tanzania and a desktop study of imported artefacts in ports from Kenya to Mozambique. Exports from Africa included ivory, gold, and slaves in exchange for beads, cloth, ointments, perfumes, oils, syrups, and decorated bowls from the Middle East, Indian subcontinent and Far East. The changes in quantities of imported vessels in different settlements suggests that the north Swahili coast, from Lamu to Unguja (Zanzibar), was used by vessels from the Middle East and western India and included Swahili trans-shipment ports for vessels coming from and going to the south Swahili coast. The proportion of Far East ceramic to Middle East is greater in the southern Swahili coast, reflecting more valuable items or an alternative route from southern India to Madagascar. A zone of low imports south of Unguja and north of Comoros that includes Kilwa suggests less interest in the trade or a border zone between Middle Eastern- and Austronesian-influenced trading areas. Large proportions of imported pot at Comoros and glass beads in Mozambique suggest that the Comoros was a port of call on the trade route to Chibuene in Mozambique, where inland trade routes met the coast. The difference in maritime and imported artefacts between Bagamoyo and Kilwa, in the high and low import zone, suggest, respectively, alternative outlooks and reliability on the sea as an area of resources, trade and transport.